ChemInform Abstract: Recent Advances in the Synthesis of Tetrahydrofurans and Applications in Total Synthesis. Issue 37 (25th August 2016) - de la Torre, Aurelien; Cuyamendous, Claire; Bultel‐Ponce, Valerie; Durand, Thierry; Galano, Jean‐Marie; Oger, Camille
Abstract: Review: 210 refs.